2009
DOI: 10.1016/j.bcp.2009.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy and estrogen treatment modulate iron metabolism in rat adipose tissue

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Page 1 of 30A c c e p t e d M a n u s c r i p Grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 46 publications
7
17
1
Order By: Relevance
“…These findings are consistent with previous reports, which have shown that E2 downregulates hepcidin synthesis and increases systemic iron availability [9][10][11][12][13][14][15][16]. The ability of E2 to perturb iron homeostasis was more evident at high doses (Figures 1,3,4,5 and 6), which is consistent with the observation that elevated, rather than physiologic, levels of E2 associate with increased systemic iron availability [9][10][11][12][13][14][15][16]42]. As reported previously [12], E2-driven changes in iron status relates to the need to compensate for E2-triggered iron loss though menstruation and E2-dependent pregnancy in premenopausal women.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are consistent with previous reports, which have shown that E2 downregulates hepcidin synthesis and increases systemic iron availability [9][10][11][12][13][14][15][16]. The ability of E2 to perturb iron homeostasis was more evident at high doses (Figures 1,3,4,5 and 6), which is consistent with the observation that elevated, rather than physiologic, levels of E2 associate with increased systemic iron availability [9][10][11][12][13][14][15][16]42]. As reported previously [12], E2-driven changes in iron status relates to the need to compensate for E2-triggered iron loss though menstruation and E2-dependent pregnancy in premenopausal women.…”
Section: Discussionsupporting
confidence: 83%
“…In that, while ovariectomy in mammals results in decreased serum iron [9], use of oral contraceptives [10] and treatment of ovariectomized mice with E2 [11,12] results in increased serum iron levels [13]. The expression of several genes involved in iron metabolism including lactotransferrin, ceruloplasmin ferroxidase, lipocalin 2 and ferroportin [12] upregulate during uterine growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Consistent with previous studies (Mattace Raso et al, 2009;Thompson et al, 1995), the OVX mice developed greater body weight than the Sham control mice (p b 0.05, Fig. 1B).…”
Section: Increased Body Weight and Tissue Weight Under Estrogen Deficsupporting
confidence: 92%
“…2A, the level of serum iron was reduced by 14.0% in the OVX group compared to the Sham group. This observation was similar to the study performed on rats, as the OVX rats had reduced serum iron and estradiol treatment could reverse this situation (Mattace Raso et al, 2009). The hepatic and splenic iron levels were increased by 26.0% and 9.5%, respectively, in the OVX mice compared to the control ( Fig.…”
Section: Altered Tissue Iron Distribution and Reduced Hemoglobin Contsupporting
confidence: 88%
See 1 more Smart Citation